Conceptualizing orientation and mobility practices within the expanded core curriculum - Malik, Shazia; Abdul Manaf, Umi Kalthom (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
This paper intends to examine the orientation and mobility practices within the Expanded Core Curriculum. The study conceptualizes and methodologically sheds light on the practices of orientation and mobility (O&M) practices within the expanded core curriculum (ECC) for visually impaired learners. O&M practices has become significant as these are essential in independence and one of the main components of the expanded core curriculum of visually impaired learners. The O&M practices are functioned in the school boundaries with O&M experts to facilitate and accommodate visually impaired learners for their better independence. However, owing to these practices, but not as a part of the expanded core curriculum, results less responsive to visually impaired learner’s needs (Aziz, 2007). Existing research has focused on O&M practices, which are the integral part of the expanded core curriculum for the independence of visually impaired but many researches were not conducted to address the O&M within the expanded core curriculum for visually impaired learners. Therefore, this study attempts to conceptualize orientation and mobility practices within the expanded core curriculum.